Guilt, Responsibility, and Denial : The Past at Stake in Post-Milošević Serbia - Gordy, Eric D., 1966- (Book collections on Project MUSE., 2013)
In one of the first studies to look at how the Yugoslav wars are understood in Serbian culture, Eric Gordy examines the legacy that confronted the country when Slobodan Miloševi? was forced out of power in 2000, assessing where transitional justice has achieved its goals, where it has not, and why it matters.